Enhancing Quality of Provider Practices for Older Adults in the Emergency Department (EQUiPPED). Issue 7 (7th April 2017) - Stevens, Melissa; Hastings, Susan N.; Markland, Alayne D.; Hwang, Ula; Hung, William; Vandenberg, Ann E.; Bryan, William; Cross, Dewayne; Powers, James; McGwin, Gerald; Fattouh, Noor; Ho, William; et al.
Abstract : EQUiPPED is a multicomponent quality improvement initiative combining education, electronic clinical decision support, and individual provider feedback to influence prescribing and improve medication safety for older adults. The objective here was to evaluate the effectiveness and sustainability of EQUiPPED to reduce the use of potentially inappropriate medications (PIMs), as defined by the American Geriatrics Society 2012 Beers Criteria, prescribed to older Veterans at the time of emergency department (ED) discharge. This evaluation represents a pre‐ and post‐intervention comparison of PIM prescriptions at 4 urban Veteran Affairs (VA) Medical Center EDs. Poisson regression was used to compare the number of PIMs prescribed to Veterans 65 years or older discharged from the ED for at least 6 months prior to the first EQUiPPED intervention at each site and for at least 12 months following the final EQUiPPED intervention. The implementation timeline varied by site depending on local resources. All 4 sites showed a significant and sustained reduction in use of PIMs. The proportion of PIMs at site one decreased from 11.9% (SD 1.8) pre‐EQUiPPED to 5.1% (SD 1.4) post‐EQUiPPED ( P < .0001); site 2 from 8.2% (SD 0.8) pre to 4.5% (SD 1.0) post ( P < .0001); site 3 from 8.9% (SD 1.9) pre to 6.1% (SD 1.7) post ( P = .0007); and site 4 from 7.4% (SD 1.7) pre to 5.7% (SD 0.8) post ( P = .04). These results suggest a multicomponent program to influence provider prescribing behavior leads to safer prescribing for older adults discharged from the ED and is sustainable across multiple VA ED sites.